Comparative efficacy of nonsteroidal anti-inflammatory drugs (NSAIDs) - Bezsheiko, Vitaliy (Psychosomatic Medicine and General Practice, 2017)
Description of the results of a meta-analysis published in "Lancet" and aimed at comparing the effectiveness of NSAIDs when used in patients with osteoarthritis of the knee and hip joint.